ARTS-INSPIRED PRACTICE: FUELLING THE IMAGINATION - Wehbi, Samantha (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2020)
As we continue to contend with complex social problems, social work practice has witnessed the need to continue to grow in seemingly unfamiliar territory. Indeed, we have seen the rise in scholarship bridging between professional disciplines such as social work and the creative arts. As we begin to understand in more depth the links and potential cross-pollination between these seemingly divergent fields, it is important to begin to crystallize our approaches in ways that help guide our community practice. The article begins by summarizing the purpose of using the arts in professional practice and proceeds to proposing a typology to conceptualize arts-inspired approaches to practice. Specifically, I propose understanding the role of art as a potential catalyst, connector, and communicator. I also propose a methodology to guide interventions by examining the modes, means, and mediums that can take our theoretical understandings of the role of art to practical application. The paper ends with an invocation to heed our anxieties about taking creative risks in our practice, not by shunning them, but by welcoming them as a way to continually grow and evolve as practitioners.